Sự khiếm nhã của khách hàng trong lĩnh vực nhà hàng - khách sạn tại TP. Hồ Chí Minh: Phân tích các tiền tố và kết quả - Ngô Quang , Huân; Nguyễn Viết , Bằng; Nguyễn Mỹ , Phúc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Along with the booming growth of the hospitality sectors in Vietnam in general and Ho Chi Minh City in particular, not only the frontline employees have to attempt to satisfy their clients but they also try to control negative emotions resulting from the rude and impolite customers. Based on a literature review on prior customer incivility studies in the whole world, this study investigates the antecedents and outcomes of this phenomenon in a developing nation as Vietnam. The paper follows a quantitative approach and the data were gathered from a sample of 477 customers dealing with employees working at hotels and restaurants in Ho Chi Minh City. The results of this study suggest that (i) Customer incivility is primarily predicted by service orientation, training/knowledge, and service representative incivility; (ii) Customer incivility was found to have a negative effect on emotional exhaustion, and capacity to satisfy customers; (iii) Emotional exhaustion was found to have a significantly negative influence on service performance, and capacity to satisfy customers.
Keywords: Customer Incivility; Emotional exhaustion; Capacity to satisfy customers; Service performance; Service orientation; Training/ Knowledge